2009
DOI: 10.1007/s10943-008-9232-8
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Spirituality, and Cancer Fatalism Beliefs on Delay in Breast Cancer Diagnosis in African American Women

Abstract: African American women are more likely than any other racial or ethnic group to present with a later stage of breast cancer at initial diagnosis. Delay in breast cancer detection is a critical factor in diagnosis at a later stage. Available data indicate a delay of 3 months or more is a significant factor in breast cancer mortalty. Numerous factors have been reported as contributing to delay in time to seek medical care including religiosity, spirituality, and fatalistic beliefs. This study examined the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 28 publications
3
88
3
1
Order By: Relevance
“…29 One study showed that women with greater delays in seeking medical care were diagnosed in advanced stages of the disease (OR=6.37, 95% CI: 2.84-14.30). 36 Another study revealed a median patient delay of 16 days, a shorter interval than that reported in our study. Another finding was that in women with well-differentiated tumors, the proportion of advanced-stage tumors did not change when the delay increased (p-trend=0.83), whereas in women with poorly differentiated tumors, this trend was monotonic (p-trend=0.03).…”
contrasting
confidence: 50%
“…29 One study showed that women with greater delays in seeking medical care were diagnosed in advanced stages of the disease (OR=6.37, 95% CI: 2.84-14.30). 36 Another study revealed a median patient delay of 16 days, a shorter interval than that reported in our study. Another finding was that in women with well-differentiated tumors, the proportion of advanced-stage tumors did not change when the delay increased (p-trend=0.83), whereas in women with poorly differentiated tumors, this trend was monotonic (p-trend=0.03).…”
contrasting
confidence: 50%
“…Among cancer patients in England, claiming to have a faith was linked to less perceived importance of health information [16]; if patients do not value health information, they may not obtain it and may therefore be less able to engage in health-protective behaviors. Over a quarter of a sample of African American women with breast cancer said they had only told God about their symptoms; these women reported greater delays in seeking medical care [52]. Samuel-Hodge et al [50] likewise noted that in African Americans with diabetes, church attendance was related to taking less action to address the illness.…”
Section: Religious Coping and Active Copingmentioning
confidence: 99%
“…In Fair et al study of 76 medically-underserved women age >40 years with inadequate follow-up imaging or biopsy (≄ 6 months since mammogram results), 48% of African-American women perceived low benefits and high barriers to follow-up from screening and care, and reported a decrease in internal health locus of control. Gullatte et al [8] and Lannin et al [9] reported that African-American women held fatalistic views, coupled with fears of finding cancer accounted for delays in follow-up from abnormal MS. Several researchers found that "wait time' in ambulatory settings prohibited follow-up from abnormal MS in African-American women [4,10,11]. Similar to the previous findings, Jones et al [12] found that 'wait time' was much longer for racial and ethnic minority patients being served in public-hospitals than private hospitals with the majority White patients (94 days vs. 77 days).…”
Section: Introductionmentioning
confidence: 99%